2020
DOI: 10.1101/2020.08.06.237305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Marcksl1 modulates endothelial cell mechanoresponse to haemodynamic forces to control blood vessel shape and size

Abstract: The formation of vascular tubes is driven by extensive changes in endothelial cell (EC) shape. Here, we have identified a novel role of the actin-binding protein, Marcksl1, in modulating the mechanical properties of EC cortex to regulate cell shape and vessel structure during angiogenesis. Increasing and depleting Marcksl1 expression level in vivo resulted in an increase and decrease, respectively, in EC size and the diameter of microvessels. Furthermore, endothelial overexpression of Marcksl1 induced ectopic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…PCs have been developed to have remote sensing, [32] phagocytic and predatory behaviors, [33,34] chemical communication, [25,35,36] and to host gene-directed protein synthesis and enzyme catalytic reactions, [37] among other features, in vitro, but have not been tested as potential delivery vectors of therapeutic agents to leukocytes in vivo. [35] We reasoned that their optimal diameter for IV delivery of anti-miR223 to immune cells of zebrafish larvae would be ≈2 μm to facilitate unhindered flow through the vas-culature (since some vessel diameters are less than 5 μm [38] ), and subsequent efficient phagocytosis by leukocytes. Thus, in our pilot studies, we systemically delivered fluorescently tagged 2 μm-diameter dextran-containing PCs, initially without anti-miR223 cargo, by IV injection either via the Duct of Cuvier or the caudal vein of 2 days post-fertilization (dpf) zebrafish larvae at increasing concentrations of proteinosomes suspended in media (Figure 2B-E).…”
Section: Injection Of Pcs Leads To Leukocyte-mediated Phagocytosis In...mentioning
confidence: 99%
“…PCs have been developed to have remote sensing, [32] phagocytic and predatory behaviors, [33,34] chemical communication, [25,35,36] and to host gene-directed protein synthesis and enzyme catalytic reactions, [37] among other features, in vitro, but have not been tested as potential delivery vectors of therapeutic agents to leukocytes in vivo. [35] We reasoned that their optimal diameter for IV delivery of anti-miR223 to immune cells of zebrafish larvae would be ≈2 μm to facilitate unhindered flow through the vas-culature (since some vessel diameters are less than 5 μm [38] ), and subsequent efficient phagocytosis by leukocytes. Thus, in our pilot studies, we systemically delivered fluorescently tagged 2 μm-diameter dextran-containing PCs, initially without anti-miR223 cargo, by IV injection either via the Duct of Cuvier or the caudal vein of 2 days post-fertilization (dpf) zebrafish larvae at increasing concentrations of proteinosomes suspended in media (Figure 2B-E).…”
Section: Injection Of Pcs Leads To Leukocyte-mediated Phagocytosis In...mentioning
confidence: 99%
“…Our lab has shown that murine yolk sac vessel remodeling depends on both vessel fusion and EC migration (Udan et al, 2013). Interestingly, live imaging studies showed distinct differences in how arterial and venous cells respond to changes in hemodynamic force (Udan et al, 2013, Kondrychyn et al, 2020, Goetz et al, 2014. These data suggest that pathways that control AV identity, which can be regulated by blood flow, may also influence physical responses of ECs to blood flow such as migration and motility that facilitate vessel remodeling.…”
Section: Introductionmentioning
confidence: 99%